Understanding the religious controversy around democracy in Muslim-majority societies: An educational perspective. Issue 1 (1st March 2020) - Saada, Najwan
This study examines the debate over the meaning and place of democracy in Arab and Muslim-majority societies as interpreted by Islamist–Salafi vs. liberal/progressive perspectives. We explore the epistemological and political tenets of both ideologies and emphasize the possible educational implications of liberal/progressive Islam in the transitional societies of the Middle East. We propose the teaching of Islam through phenomenological and cultural studies pedagogies so that students exercise their capacities of inclusive and equal citizenship, religious reasoning, reflective identities and the pursuit of the common good.